Treatment of 11 cases of juvenile idiopathic arthritis by intra-articular injection of adalimumab - Chi, Y (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2022)
Objective: To evaluate the efficacy and safety of intra-articular injection of adalimumab (ADA) in the treatment of refractory oligoarticular juvenile idiopathic arthritis (JIA). Methods: This was a retrospective study. Clinical data on age, gender, and symptoms of joint swelling and pain were collected from 11 children with refractory oligoarticular JIA involving only knee joints admitted to Department of Rheumatism and Immunology of Children's Hospital, Capital Institute of Pediatrics from November 2019 to October 2020. The physician and parent-child evaluation of disease activity, the number of active joints, and the level of erythrocyte sedimentation rate (ESR) at different treatment time points were analyzed at every 4-week observation point after drug administration, and the non-parametric Kruskal-Wallis test was used to compare the differences in clinical evaluation indicators and changes in laboratory tests at different treatment times. The follow-up period was 6 months. Results: Among the 11 children, 5 were boys and 6 were girls. The age was 3.0 (2.8) years. All 11 children had symptoms of joint swelling and pain as well as limitation of movement. After 3 intra-articular injections of ADA, the joint symptoms of 11 children were better than before treatment; the joint symptoms of 7 children disappeared completely, and no recurrence occurred during the 6-month follow-up period. At different treatment times, physician and parent-child evaluation of disease activity, a gradual decrease in the number of active joints in the children, ESR, and juvenile arthritis disease activity score with 27 joints were all statistically significant (χ2=53.99, 59.37, 32.87, 40.07, 54.00, all P<0.001).No significant adverse drug reactions were observed in any of the 11 children during treatment and follow-up. Conclusion: Intra-articular injection of ADA in the treatment of refractory oligoarticular JIA has a significant effect in controlling joint symptoms and is relatively safe